2008
DOI: 10.1002/chem.200701904
|View full text |Cite
|
Sign up to set email alerts
|

Photo Gel–Sol/Sol–Gel Transition and Its Patterning of a Supramolecular Hydrogel as Stimuli‐Responsive Biomaterials

Abstract: In a focused library of glycolipid-based hydrogelators bearing fumaric amide as a trans-cis photoswitching module, several new photoresponsive supramolecular hydrogelators were discovered, the gel-sol/sol-gel transition of which was pseudo-reversibly induced by light. Studying the optimal hydrogel by NMR spectroscopy and various microscopy techniques showed that the trans-cis photoisomerization of the double bond of the fumaric amide unit effectively caused assembly or disassembly of the self-assembled supramo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
144
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(147 citation statements)
references
References 85 publications
3
144
0
Order By: Relevance
“…Photo-switchable moieties are notably fascinating because they support the establishment of light-responsive peptide hydrogels. LMWGs comprising azobenzenes [35][36][37] and stilbenes 26,38,39 are two important variations of this approach. Azobenzene is unique since it can be readily photo-isomerized as well as form photo-responsive inclusion complex with b-CD via host-guest interaction in water.…”
mentioning
confidence: 99%
“…Photo-switchable moieties are notably fascinating because they support the establishment of light-responsive peptide hydrogels. LMWGs comprising azobenzenes [35][36][37] and stilbenes 26,38,39 are two important variations of this approach. Azobenzene is unique since it can be readily photo-isomerized as well as form photo-responsive inclusion complex with b-CD via host-guest interaction in water.…”
mentioning
confidence: 99%
“…For example, Huang et al [201] reported the method to fabricate hierarchical one-dimensional (1D) hydrogels architectures including nanotubes, coiled-coil ropelike structures, nanohelices, and nanoribbons via lanthanum-cholate supramolecular self-assembly, mediated by temperature. Besides, hydrogel patterns at micron scale or macro scale can also be obtained via supramolecular self-assembly [202][203][204]. These structured supramolecular hydrogels were anticipated to generate versatile applications in cell culture, tissue engineering, biomedical science and biosensor.…”
Section: Supramolecular Self-sssemblymentioning
confidence: 99%
“…In the course of the research of Hamachi and coworkers on organo-and hydrogelators based on glycosylated amino acids, Matsumoto and coworkers [75] synthesized a variety of compounds based on fumaric acid diamide to obtain photo-responsive hydrogels (Scheme 11.22). Some of the compounds did form photo-responsive hydrogels: their solutions underwent a gel-to-sol transition upon E-to-Z photoisomerization and vice versa.…”
Section: Photo-responsive Systemsmentioning
confidence: 99%